Pendidikan Multikultural: Menuju Kesatuan Melalui Keanekaragaman - Gusnia Fatimah Azzahra; Masduki Asbari; Annisa Shintya Ariani (AGUSPATI RESEARCH INSTITUTA, 2023)
Multicultural education has become a crucial cornerstone in shaping a diverse and cohesive society today. The objective of this study is to explore and analyze the role of multicultural education in culturally diverse communities, backgrounds, and identities. This report utilizes a qualitative descriptive method with note-taking as the data collection technique, as the data source involves listening to oral narratives from the YouTube channel